Optimizing qPlus sensor assemblies for simultaneous scanning tunneling and noncontact atomic force microscopy operation based on finite element method analysis - Omur E. Dagdeviren (Beilstein Journal of Nanotechnology, 2017)
Quartz tuning forks that have a probe tip attached to the end of one of its prongs while the other prong is arrested to a holder (“qPlus” configuration) have gained considerable popularity in recent years for high-resolution atomic force microscopy imaging. The small size of the tuning forks and the complexity of the sensor architecture, however, often impede predictions on how variations in the execution of the individual assembly steps affect the performance of the completed sensor. Extending an earlier study that provided numerical analysis of qPlus-style setups without tips, this work quantifies the influence of tip attachment on the operational characteristics of the sensor. The results using finite element modeling show in particular that for setups that include a metallic tip that is connected via a separate wire to enable the simultaneous collection of local forces and tunneling currents, the exact realization of this wire connection has a major effect on sensor properties such as spring constant, quality factor, resonance frequency, and its deviation from an ideal vertical oscillation.